Les images des villes brésiliennes dans les manuels scolaires de France et du Brésil : entre mythes et réalités - Leonardo Moreira Ulhôa (Confins)
This text proceeds from some reflections about images of Brazilian cities illustrating geography textbooks used in educational institutions of France Brazil. By fixing, immobilizing, and ritualizing certain models of photographic images - so-called "mummified" - particular aspects are prioritized and generalized in terms of reality. In order to know the reality of Brazilian cities it is necessary to preconceive that the figures and texts that are part of the textbooks iconography are only parts of a whole. From this assumption, we believe that the image cannot be considered as an accurate reduction of reality.